(untitled) (KULT_online, 2021)
Anaïs Angelo’s recent biography of Jomo Kenyatta, Power and the Presidency in Kenya, is as illustrative of Kenya’s first president as it is of the executive office that outlives his presidency. Angelo argues that Kenyatta’s “discreet and distant” political style paired with his ambiguous relationship to Mau Mau enabled Kenyatta to unite Kenya without a nationalist vision. While he remained distant from the technical aspects of rule, rather delegating them to others, Kenyatta’s authority over national resources consolidated during his presidency.